Peran Kepala Sekolah Sebagai Administrator dan Supervisor - Hamidi Hamidi; Nuzuwar Nuzuwar; Ifnaldi Nurmal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to find out how the role of the principal as an administrator and supervisor. The design of this study uses a qualitative descriptive approach. The research subjects consisted of principals, teachers and staff staff at Megang Sakti Public Middle School, Musi Rawas District. The results of the study explained that the principal had applied his main tasks and functions as the principal. The conclusions of this study are that the Principal of Megang Sakti Middle School has made a good work program, this can be seen from school activities, both related to students and with educators and school education. Keywords: Work Program, Role of Principal